PEMBELAJARAN KEAKSARAAN FUNGSIONAL DAN KECAKAPAN HIDUP WARGA BELAJAR - Muhsin, Mokhamat (JIV-Jurnal Ilmiah Visi, 2006)
Having been developed for years, a program on literacy is one of nonformal education one of objectives is to improve the quality of life of the society. The research raises questions on (1) whether the existing literacy program provides its participants with life skill improvement reality, (2) whether practicing the skills would improve the quality of their life. Being akcnowledge of the program, the head of subdistrict responds positively to its progress.